The cytokines HGF and CXCL13 predict the severity and the mortality in COVID-19 patients - Matthieu Perreau (Nature Portfolio, 2021)
Infection with SARS CoV2 results in the induction of multiple cytokine and inflammatory pathways. Here the authors demonstrate the association of HGF and CXCL13 production with increased severity and mortality in COVID-19 patients.